Short-term Outcomes following Concussion in the NFL: An 11-year Retrospective Study of Player Release Rate and Financial Loss. Issue 7 (21st July 2017) - Ramkumar, Prem; Navarro, Sergio Michael
Objectives: The primary goal of this study was to assess the short-term outcomes among National Football League (NFL) players following concussion in terms of: (1) DNP protocol activation, (2) release rate at one and three years, and (3) mean salary reduction. A secondary goal of the study was to stratify the post-concussive release rate by franchise and player position. Methods: NFL player transaction records and publicly available weekly injury reports from August 2005 to January 2016 for NFL players were analyzed. All players immediately sustaining recorded concussions were evaluated for a change to inactive or do-not-play (DNP) status. The one-year and three-year release rate following concussion was defined as any player transitioning to inactivation, retirement, free agency, or any failure to return for a successive season on the same team's active roster after one or three years from the initial concussion. Student's t-test was used to compare release rates between non-concussed and concussed players at one and three years. Mean salary reduction per year following concussion was calculated using publicly available player contracts. Additionally, franchise-level and position-based analyses of the release rate were performed. Results: Of the total 5, 451 NFL players retrospectively analyzed over the 11-year period, 373 sustained publicly reported concussions resulting in DNP protocol activation. The release rate of the post-concussive versus non-concussive player was 26% vs. 20% at 1 year (p<0.01) and 31% vs. 19% at 3 years (p<0.01). After analyzing individual player contracts, the mean year-over-year change in contract value for concussed players after DNP protocol activation was an overall salary reduction of 760, 000/year ± 2, 380, 000. Figure 1 depicts the tendency of each NFL franchise to release an athlete following concussion within one and three years. Table 1 reports a position-based analysis in terms of concussion rate, mean salary reduction, and NFL career longevity. Conclusion: Our retrospective study demonstrates that NFL concussions resulting in DNP protocol activation leads to a statistically greater release rate among concussed NFL players than non-concussed players. Released players suffered reduction in year-over-year accumulated earnings, and particular franchises tended to release concussed players more than others. Position-based Concussion Statistics of Players by DNP Activation, Salary Reduction, Career Length Position Group DNP Concussions Mean Salary Reduction (/yr) Average Career Length (yrs) DB 75 (20.1%) 280, 000 7.0 WR 66 (17.7%) 1, 760, 000 7.3 OL 49 (13.1%) 1, 190, 000 5.5 TE 46 (12.3%) 333, 000 7.7 RB 40 (10.7%) 140, 000 5.1 LB 39 (10.5%) 720, 000 4.9 DL 31 (8.3%) 540, 000 7.0 QB 27 (7.2%) 2, 440, 000 7.3 Total 373 760, 000 6.4